2014
DOI: 10.3390/ijms15011625
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Partially Prevents Rotenone-Induced Neurotoxicity in Dopaminergic SH-SY5Y Cells through Induction of Heme Oxygenase-1 Dependent Autophagy

Abstract: Parkinson disease (PD) is a complex neurodegenerative disorder characterized by a progressive loss of dopaminergic neurons. Mitochondrial dysfunction, oxidative stress or protein misfolding and aggregation may underlie this process. Autophagy is an intracellular catabolic mechanism responsible for protein degradation and recycling of damaged proteins and cytoplasmic organelles. Autophagic dysfunction may hasten the progression of neuronal degeneration. In this study, resveratrol promoted autophagic flux and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 66 publications
(75 reference statements)
3
85
0
Order By: Relevance
“…SES (100 µM) alone treated cells show no alterations in nuclear morphology and are similar to vehicle control. Lin et al reported that resveratrol, a polyphenolic stilbene prevented nuclear damage induced by ROT [42] and this correlates with our study.…”
Section: Resultssupporting
confidence: 93%
“…SES (100 µM) alone treated cells show no alterations in nuclear morphology and are similar to vehicle control. Lin et al reported that resveratrol, a polyphenolic stilbene prevented nuclear damage induced by ROT [42] and this correlates with our study.…”
Section: Resultssupporting
confidence: 93%
“…Resveratrol (RSV) is a naturally occurring polyphenolic phytoalexin that is produced by polygonum cuspidatum, mulberry (Morus species), grapes, and red wine. It has diverse biological activities including anti-oxidation [21] , anti-cancer [22] , anti-inflammation [23] , cardioprotection [24] , and neuroprotection [25] . Several reports indicate that RSV is capable of preventing and treating diabetes and its related complications [26,27] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, carnosic acid protects against 6-hydroxydopamine (6-OHDA)-induced apoptosis by inducing autophagy in SH-SY5Y cells [35]. Similarly, resveratrol protects against rotenone-induced neuronal apoptosis by regulating autophagic flux [36]. …”
Section: Introductionmentioning
confidence: 99%